2021
DOI: 10.1101/2021.06.19.449131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual stimulation induces distinct forms of sensitization of On-Off direction-selective ganglion cell responses in the dorsal and ventral retina

Abstract: Experience-dependent modulation of neuronal responses is a key attribute in sensory processing. In the mammalian retina, the On-Off direction-selective ganglion cell (On-Off DSGC) is well known for its robust direction selectivity. However, how the On-Off DSGC light responsiveness dynamically adjusts to the changing visual environment is underexplored. Here, we report that the On-Off DSGC can be transiently sensitized by prior stimuli. Notably, distinct sensitization patterns are found in dorsal and ventral DS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Previous works have shown that inhibitory synapses can be depressing [16, 15, 23]. In particular, glycinergic synapses that input to bipolar cells can be depressing [14]. However, there is no method to experimentally remove the depressing nature of the synapse without affecting the inhibitory weight, so we could not show experimentally that the depressing nature of the synapse is necessary to the OSR.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous works have shown that inhibitory synapses can be depressing [16, 15, 23]. In particular, glycinergic synapses that input to bipolar cells can be depressing [14]. However, there is no method to experimentally remove the depressing nature of the synapse without affecting the inhibitory weight, so we could not show experimentally that the depressing nature of the synapse is necessary to the OSR.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous reports have shown that inhibitory synapses can be depressing, i.e. have a decreasing weight depending on previous inputs [18, 36, 23, 17, 14]. It has been hypothesized that the variation in synaptic strength results from varying availability of vesicles in the readily releasable vesicle pool, which gets gradually depleted upon persistent inputs [31, 5, 25].…”
Section: Resultsmentioning
confidence: 99%